Implementasi Metode FIS Mamdani Pada Aplikasi Jadwal Mengajar Guru Di SMK Adi Luhur 2 Jakarta - Imam Sunoto; Lukman Lukman (PETIR, 2019)
Scheduling subjects in a school can support, facilitate and enhance the quality of a school. Subject scheduling generally functions for activities in facilitating the quality of teaching teachers and students in order to create discipline in school performance activities. Along with increasing hours of subjects that require precise and fast accuracy in processing data can also speed up time. In general, the data processing of scheduling subjects at Adi Luhur 2 Vocational School 2 is still done manually and there is often a lack of schedule due to the teacher being absent or teaching in school, so a computerized information system is needed where everything can be done correctly. For that we need a system that can determine the scheduling of subjects so that there is no conflict with other teaching schedules. In this study, Mamdani's fuzzy infrence system (fis) logic is used. With the existence of a teaching schedule management system with fuzzy mamdani method approach more accurately in accordance with the best conditions of the teacher concerned. The results of this study are in the form of a prototype that can process input in the form of teacher's willingness to arrange teaching schedules at Adi Luhur 2 Vocational School Jakarta.